Adaptação transcultural e validação do the Fremantle Neck Awareness Questionnaire (FreNAQ) para o português brasileiro em indivíduos com dor cervical crônica - Apahaza, Gabriel Henrique Santin (2023)
The FreNAQ is a psychometrically satisfactory instrument. This is an instrument that assesses the body perception of patients with chronic neck pain. Since it is simple to apply, low cost and resource for application, it becomes a viable tool of wide exploratory and complementary range for the evaluation of patients with chronic neck pain, identifying the patient's condition and being a possible prescriber of therapeutic interventions for improvement of the conditions of these patients. It favors the approach of clinicians and researchers in improving the understanding of the perception of the cervical spine in individuals with chronic neck pain in the Brazilian population and understanding of factors that may not only lead to the belief that the cervical spine is functionally compromised, but also to a cycle of negative beliefs and expectations about chronic pain. The sample size was set at 130 participants. Thirty of these participants were involved in obtaining the final version of the Brazilian Portuguese FreNAQ. The other 100 volunteers had their data used for structural and construct validity analysis. Data from 50 participants were used for reliability and internal consistency analysis. To carry out a comparative analysis, the following complementary assessment instruments were selected: Numerical Pain Scale (END), 36-item short form survey (SF-36), Neck Disability Index (NDI), Pain Catastrophizing Scale (ECD), Scale kinesiophobia cover (ETC). Thus, the internal consistency was calculated using Cronbach's alpha to verify the presence of redundant and heterogeneous items, considering the variation between 0.70 and 0.95 as adequate values. Reliability was assessed using the test-retest model using the intraclass correlation coefficient (ICC2.1), 95% confidence interval (CI), measurement standard error (MPE), and minimum detectable difference (DMD). ceiling and floor were analyzed in the study. These effects are present when 15% of the sample reaches the minimum or maximum values of the questionnaire's total score. Most research participants were women, married, with average weight, physically inactive, and postgraduate level masters. The values presented about reliability were substantial (values between 0.75 and 0.90). Regarding internal consistency, the values were considered adequate (values between 0.70 and 0.95). However, regarding the error, the values were considered harmful (EPM=32.83%). To analyze the construct validity, the final FreNAQ score was correlated with the scores of the other instruments used in the study (END, NDI, ECD, SF-36, ETC). Of all the correlations analyzed, only those between the FreNAQ and the assessment instruments: SF-35 (general health status domain), ETC did not present a statistically significant correlation. The ceiling and floor effects showed 16% and 2%, respectively. Demonstrating the presence of a ceiling effect 1% above the reference values. The Brazilian Portuguese version of FreNAQ has adequate reliability, internal consistency, and validation properties. Therefore, no need to carry out future analyses regarding the structure.